1993
DOI: 10.1136/gut.34.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin-6 in mediating the acute phase protein response and potential as an early means of severity assessment in acute pancreatitis.

Abstract: A number of laboratory and clinical studies have shown that interleukin-6 is the principal mediator of the acute phase protein response. In this study the relationship between serum concentrations of interleukin-6 and C-reactive protein in acute pancreatitis are examined and the ability of interleukin-6 to discriminate between severe and mild attacks is assessed. We have studied 24 patients (10 severe and 14 mild). Serum samples were collected on admission, six hourly for 48 hours and then 12 hourly for a furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(124 citation statements)
references
References 25 publications
7
112
1
4
Order By: Relevance
“…It has long been known that the changes occurring in the liver and in other organs during the acute phase response are coordinated by signals generated at the site of injury, among which several cytokines have been well characterized, including IL-1, IL-6, TNF␣, IFN␥, leukemia inhibitory factor, IL-11, and oncostatin M. These proteins are locally produced by the tissue and by circulating mononuclear cells in response to prototype inflammatory stimuli and can elicit the diverse biological effects characteristic of the acute phase response. Interestingly, during the acute phase of pancreatitis, levels of cytokines are strongly increased in serum (9). In the current study, we have evaluated the respective contributions of several cytokines and of dexamethasone to the transcriptional induction of the rat PAP I gene in vitro, using a rat pancreatic acinar cell line.…”
mentioning
confidence: 99%
“…It has long been known that the changes occurring in the liver and in other organs during the acute phase response are coordinated by signals generated at the site of injury, among which several cytokines have been well characterized, including IL-1, IL-6, TNF␣, IFN␥, leukemia inhibitory factor, IL-11, and oncostatin M. These proteins are locally produced by the tissue and by circulating mononuclear cells in response to prototype inflammatory stimuli and can elicit the diverse biological effects characteristic of the acute phase response. Interestingly, during the acute phase of pancreatitis, levels of cytokines are strongly increased in serum (9). In the current study, we have evaluated the respective contributions of several cytokines and of dexamethasone to the transcriptional induction of the rat PAP I gene in vitro, using a rat pancreatic acinar cell line.…”
mentioning
confidence: 99%
“…This results in an imbalance between pro-and anti-inflammatory cytokines, resulting in the development of SIRS. Some mediators, such as TNF-alpha, phospholipase, and kinin, are increased greatly in animal models of SAP [9] , and some studies have shown that there is a significant correlation between the serum levels of IL-1-beta, IL-6, IL-8, IL-10 and IL-11 and the severity of acute pancreatitis [24][25][26][27] . Animal studies have shown that early blockade of the cytokine cascade at the level of the IL-1 receptor significantly decreases the severity of pancreatitis and intrinsic pancreatic damage, as well as the mortality from SAP [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Hallazgos similares son los obtenidos por Heresbach (30) y Mayer (18), aunque la mayoría de las publicaciones detectan los valores máxi-mos antes de las 48 horas (31)(32)(33)(34)(35). En cualquier caso, la IL-6 es considerada la más útil clínicamente como marcador de gravedad (35)(36)(37)(38)(39). Algunos estudios sugieren que la asociación de IL-6 y lipasa pudieran ser buenos parámetros de diagnóstico y pronóstico en la práctica clí-nica diaria (34).…”
Section: Discussionunclassified